ANALISIS USULAN PERBAIKAN MUTU PRODUK BERDASARKANMETODE SEVEN TOOLS DI PT. X - Muzakir Muzakir (Jurnal Optimalisasi, 2016)
Have done analyzing the proposed improvement of product quality by method Seven Tools. From the calculation and analysis tools with seven methods that have been done there are three defects that occur on the production floor with the number of product defects due to a loose assembly of 196 pieces with a percentage of 59.57%, and disability as a result of gluing the loose many as 82 pieces of disability (24, 92%), the smallest of disability by 51 disability (15.50%) which is due to lack of good raw material. The cause product defects occur due to human factors, machine, material, method, and the work environment, so that it can be said that the process is out of control. By using Seven tools in controlling the quality of products, can know and minimize the occurrence of product defects so that the quality and product quality under control.Keywords : Seven tools, product quality, disability.